ChemInform Abstract: Computational Modelling of Oxygenation Processes in Enzymes and Biomimetic Model Complexes. Issue 8 (25th February 2014) - de Visser, Sam P.; Quesne, Matthew G.; Martin, Bodo; Comba, Peter; Ryde, Ulf
Abstract Review: 108 refs.